Tax Planning Implementation on Income Tax, Article 23 as A Legal Effort To Minimize Tax Expense Payable - Achmad Daengs GS (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
An effort to minimize tax burden can be done in various ways start from inside the scope of taxation regulation to violate the taxation regulation. This research focuses on related Laws with the efforts to minimize Income tax. In general tax planning referred to engineered the business process and tax payer transaction. The aim is tax payable in minimal number but under taxation regulation scope. The outline of this study focus on planning effort of Tax Income Article 23 to minimize tax expense payable run in PT. TRIPERKASA AMININDAH Surabaya. Tax planning that done in this company refer to provision  in accordance with  Directorate General of Tax Decision Number : Kep-305/PJ/2001 on the estimates of nett income. Tax planning had done by this company in addition to refer the regulation also based on the condition of this company which experiencing poor performance. Then the aim that will be reached from that tax planning to reach minimal expense over the Income Tax Article 23 it can be done with gross up method. From the analysis result on the alternative it can draw a conclusion that PT. TRIPERKASA AMININDAH  Surabaya  has made adjustments on the regulation above, calculation of Income Tax Article 23 with gross up method in fact be able to saving the tax then suitable with the tax planning aim that is effort to minimize tax expense payable.